Linking nutrient sensing, mitochondrial function, and PRR immune cell signaling in liver disease. Issue 11 (November 2022) - Kemper, Claudia; Sack, Michael N.
Highlights: Nonalcoholic fatty liver disease (NAFLD) and nonalcoholic hepatic steatohepatitis (NASH) are on the rise, and therapeutics to successfully target these detrimental conditions are very limited. Nutrient-induced hepatic lipid overload across cells in the mammalian liver contributes to mitochondrial dysfunction, producing damage-associated molecular patterns (DAMPs) that initiate hepatosteatosis. Pattern recognition receptors (PRRs) integrate mitochondrial perturbations into proinflammatory cellular behavior in mammalian liver parenchymal cells and immune cells, supporting NAFLD pathogenesis and progression to NASH. Intracellular components of the canonical PRR system, complement (the complosome), operate across a range of cells in humans and mice, and may contribute to NAFLD/NASH pathogenesis. Pharmacologically targeting nutrient–mitochondria–PRR pathways, including intracellularly active complement, might lead to new putative NAFLD/NASH treatments. Abstract : Significance: The mechanistic understanding of the recently identified functional interplay between nutrient sensing, mitochondrial activity, classic PRR, and intracellular complement activation across cell populations may help to uncover novel therapeutic intervention targets to treat nonalcoholic fatty liver disease. Abstract : Caloric overconsumption in vertebrates promotes adipose and liver fat accumulation while perturbing the gut microbiome. This triad triggers pattern recognition receptor (PRR)-mediated immune cell signaling and sterile inflammation. Moreover, immune system activation perpetuates metabolic consequences, including the progression of nonalcoholic fatty liver disease (NAFLD) to nonalcoholic hepatic steatohepatitis (NASH). Recent findings show that sensing of nutrient overabundance disrupts the activity and homeostasis of the central cellular energy-generating organelle, the mitochondrion. In parallel, whether caloric excess-initiated PRR signaling and mitochondrial perturbations are coordinated to amplify this inflammatory process in NASH progression remains in question. We hypothesize that altered mitochondrial function, classic PRR signaling, and complement activation in response to nutrient overload together play an integrated role across the immune cell landscape, leading to liver inflammation and NASH progression.